2014
DOI: 10.1242/dev.093526
|View full text |Cite
|
Sign up to set email alerts
|

Ccm3, a gene associated with cerebral cavernous malformations, is required for neuronal migration

Abstract: Loss of function of cerebral cavernous malformation 3 (CCM3) results in an autosomal dominant cerebrovascular disorder. Here, we uncover a developmental role for CCM3 in regulating neuronal migration in the neocortex. Using cell type-specific gene inactivation in mice, we show that CCM3 has both cell autonomous and cell nonautonomous functions in neural progenitors and is specifically required in radial glia and newly born pyramidal neurons migrating through the subventricular zone, but not in those migrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 94 publications
0
30
0
1
Order By: Relevance
“…Patients with PDCD10 mutations had an increased number of lesions and also presented with lesion hemorrhages earlier in life. Moreover, these authors found additional PDCD10 aberrations in addition to the CCMs, including scoliosis, cognitive disability, and skin lesions, further suggesting that PDCD10 plays other roles in tissue development aside from endothelial cell formation (43, 44). …”
Section: Additional Developmentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients with PDCD10 mutations had an increased number of lesions and also presented with lesion hemorrhages earlier in life. Moreover, these authors found additional PDCD10 aberrations in addition to the CCMs, including scoliosis, cognitive disability, and skin lesions, further suggesting that PDCD10 plays other roles in tissue development aside from endothelial cell formation (43, 44). …”
Section: Additional Developmentsmentioning
confidence: 96%
“…Louvi et al discovered that PDCD10 has a pivotal role in neuronal migration via suppression of RhoA signaling. They demonstrated that PDCD10 activity is required for proper radial glia and pyramidal neuron migration through the subventricular zone (43). Loss of PDCD10 resulted in dysregulation of the actin and microtubule cytoskeleton and adversely affected cellular morphology and migration.…”
Section: Additional Developmentsmentioning
confidence: 99%
“…CCM3 geninin knock-out (ortadan kaldırılması) edilmesine dayalı çalışmalarda, kortikal tabakalanmalarda incelmelerin olduğu ve bu durumun yetişkin farelerde de devam ettiği belirlenmiştir. In vitro ve in vivo çalışmaların sonuçları, günümüzde CCM3'ün nöronal morfolojiyi etkileyebileceğini söylememize imkân sağlamaktadır (38).…”
Section: Ccm2unclassified
“…Treatment options include observation of asymptomatic lesions, antiepileptic medication, and surgical excision of lesions in patients with symptomatic or repetitive hemorrhages or intractable seizures; however pharmacological therapies that improve outcome are lacking. CCM disease is usually sporadic, although 20% of patients carry lossof-function mutations in one of three genes: CCM1 (also known as "KRIT1"), CCM2, and CCM3 (also known as "PDCD10") (3), which encode structurally unrelated cytoplasmic proteins with critical roles in endothelial cells (4) and, uniquely for CCM3, in neurons and astrocytes as well (5,6). CCM3 loss in neural progenitors results in hyperproliferation/activation of brain astrocytes and enhanced activity of RhoA in vivo and increased proliferation and survival of primary astrocytes in vitro (5,6).…”
mentioning
confidence: 99%
“…CCM disease is usually sporadic, although 20% of patients carry lossof-function mutations in one of three genes: CCM1 (also known as "KRIT1"), CCM2, and CCM3 (also known as "PDCD10") (3), which encode structurally unrelated cytoplasmic proteins with critical roles in endothelial cells (4) and, uniquely for CCM3, in neurons and astrocytes as well (5,6). CCM3 loss in neural progenitors results in hyperproliferation/activation of brain astrocytes and enhanced activity of RhoA in vivo and increased proliferation and survival of primary astrocytes in vitro (5,6). We took advantage of these well-defined cellular phenotypes of CCM3 loss to explore potential pharmacological treatment options for CCM.…”
mentioning
confidence: 99%